(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Matrix Rhythm concept is founded on the premise that all cellular actions, whether preventive, therapeutic, regenerative, or destructive, operate largely through the cell's environment. The frequency of pulsation in muscle cells is 8-12 Hertz. Outside of the 8-12 Hertz range, muscle pulsation frequency is linked to aches, muscle tension, and other health issues. Variations in pulse frequency and the logistics of the life process at the cellular level are linked to changes in muscle flexibility and plasticity. Specific vibrations in skeletal muscles and the nervous system are activated and rebalanced by the MRT. The MRT generates an oscillating rhythm that increases lymphatic venous perfusion of the extracellular space, in which the anti-edematous benefits occur. We reviewed the Matrix Rhythm Therapy procedures in treating various pathological disorders in this research.Matrix rhythm therapy is useful in treating complaints such as enhancing Range of motion, increase in muscle strength and lowering in pain, according to the result of this research. In terms of physical health, functional outcomes, and satisfaction, matrix rhythm therapy delivers long- term benefits for those with frozen shoulder and leprosy.